Running Promotes Transformation of Brain Astrocytes Into Neuroprotective Reactive Astrocytes and Synaptic Formation by Targeting Gpc6 Through the STAT3 Pathway - Chen, Zhe; Gao, Meng; Su, Yanlin; Liu, Pengran; Sun, Binlei (Frontiers in Physiology, 2021)
Ischemic stroke is a disease caused by cerebral ischemia upon the blockage of an artery, which results in a very high disability rate. Currently, there are few studies on the mechanism of astrocyte function in cerebral ischemia. In this study, we investigated the effect of exercise on the transformation of astrocytes toward the neuroprotective phenotype through the STAT3–Gpc6 axis, and the subsequent promotion of synaptic formation. Through in vivo study of middle cerebral artery occlusion after exercise, we found that running can promote the transformation of astrocytes toward the neuroprotective phenotype. In vitro experiments, in which oxygen-glucose deprivation method was used to treat astrocytes after exercise, revealed that the astrocytes transformed into neuroprotective astrocytes, and that the expression levels of STAT3 and Gpc6 were increased. We confirmed that mechanistically, exercise can target Gpc6 through the STAT3 pathway and then regulate the number of synapses. We conclude that running can promote synaptic proliferation by polarizing astrocytes toward the neuroprotective phenotype, ultimately leading to nerve regeneration.